Gambaran Pengetahuan Ibu Nifas Tentang Anemia di RSU Nur Hidayah - Prabawati, Sulistyaningsih; Melina, Fitria; Diniati, Diniati (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2024)
Background: Anema is a condition where the number of red blood cells or hemoglobin concentration in them is lower than normal. According to WHO in 2021, the incidence of anemia in postpartum mothers is 56%. At Nur Hidayah Hospital the number of postpartum mothers from May-June is 81. Knowledge is everything that is known and guidelines for shaping one's actions. Objective: To determine the knowledge of postpartum mothers regarding anemia guidance at Nur Hospital Research Methods: This research is (quantitative research). The population in this research is 81 people. The sampling technique uses non-probability sampling in the form of accidental sampling. The sample size obtained was 30 respondents. The instrument in this research is a questionnaire using data analysis methods wivariat Research Results: The frequency distribution of postpartum mothers' knowledge based on knowledge about the meaning of anemia is in the good category (70.0%). The knowledge of postpartum mothers about the causes of anemia is in the sufficient category (80.0%). Postpartum mothers' knowledge about the signs and symptoms of anemia is in the sufficient category (93.3%). Postpartum mothers' knowledge about the classification of anemia is in the sufficient category (93.3%) Postpartum mothers' knowledge about the impact of anemia is in the sufficient category (76.7%) Conclusion: Ifas mothers' knowledge about anenua at Nur Hidayah Hospital is in the sufficient category